To Automate the Services Life Cycle of Cloud Using Semantic Technologies (International Journal of Engineering and Computer Science, 2015)
Cloud computing is an emerging computing paradigm in which resources of the computing infrastructure. As promising as it is, this paradigm also brings forth many new challenges for data security and access control when users outsource sensitive data for sharing on cloud servers in which they are not in the same domain as data owners. To retain delicate user data privileged against untrusted servers, survive solutions commonly uses cryptographic methods by disclosing data decryption keys only to authorized users. In Proposed prototype, the service attributes are like service cost, backup rules, storage size, and service availability. Specification details like quality of data, security levels that are accepted for the service software. To show however this life cycle will change the usage of cloud services, we have a tendency to describe a cloud storage epitome that we have developed. We have divided the IT service life cycle into five phases those are requirements, discovery, negotiation, composition, and consumption